Mitochondrial Creatine Kinase Attenuates Pathologic Remodeling in Heart Failure. Issue 5 (4th March 2022) - Keceli, Gizem; Gupta, Ashish; Sourdon, Joevin; Gabr, Refaat; Schär, Michael; Dey, Swati; Tocchetti, Carlo G.; Stuber, Annina; Agrimi, Jacopo; Zhang, Yi; Leppo, Michelle; Steenbergen, Charles; et al.
Abstract : Background: Abnormalities in cardiac energy metabolism occur in heart failure (HF) and contribute to contractile dysfunction, but their role, if any, in HF-related pathologic remodeling is much less established. CK (creatine kinase), the primary muscle energy reserve reaction which rapidly provides ATP at the myofibrils and regenerates mitochondrial ADP, is down-regulated in experimental and human HF. We tested the hypotheses that pathologic remodeling in human HF is related to impaired cardiac CK energy metabolism and that rescuing CK attenuates maladaptive hypertrophy in experimental HF. Methods: First, in 27 HF patients and 14 healthy subjects, we measured cardiac energetics and left ventricular remodeling using noninvasive magnetic resonance 31 P spectroscopy and magnetic resonance imaging, respectively. Second, we tested the impact of metabolic rescue with cardiac-specific overexpression of either Ckmyofib (myofibrillar CK) or Ckmito (mitochondrial CK) on HF-related maladaptive hypertrophy in mice. Results: In people, pathologic left ventricular hypertrophy and dilatation correlate closely with reduced myocardial ATP levels and rates of ATP synthesis through CK. In mice, transverse aortic constriction-induced left ventricular hypertrophy and dilatation are attenuated by overexpression of CKmito, but not by overexpression of CKmyofib. CKmito overexpression also attenuates hypertrophy after chronic isoproterenol stimulation. CKmito lowers mitochondrial reactive oxygen species, tissue reactive oxygen species levels, and upregulates antioxidants and their promoters. When the CK capacity of CKmito-overexpressing mice is limited by creatine substrate depletion, the protection against pathologic remodeling is lost, suggesting the ADP regenerating capacity of the CKmito reaction rather than CK protein per se is critical in limiting adverse HF remodeling. Conclusions: In the failing human heart, pathologic hypertrophy and adverse remodeling are closely related to deficits in ATP levels and in the CK energy reserve reaction. CKmito, sitting at the intersection of cardiac energetics and redox balance, plays a crucial role in attenuating pathologic remodeling in HF. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT00181259. Abstract : Supplemental Digital Content is available in the text.